THE ROLE AND BIOMARKER VALUE OF IL-17 AND IL-23 CYTOKINES IN LABORATORY DIAGNOSIS OF AXIAL SPONDYLOARTHRITIS - Kurbonova Zumrad Chutbayevna; Saidrasulova Gulizebo Baxtiyorovna; Toshimova Shahnoza Hoshimjon qizi (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Axial spondyloarthritis (axSpA) is a chronic inflammatory rheumatic disease characterized by predominant involvement of the spine and sacroiliac joints. The disease is associated with inflammatory back pain, stiffness, enthesitis, and progressive structural changes including syndesmophyte formation and ankylosis. Recent studies highlight the important role of the IL-23/IL-17 inflammatory axis in the pathogenesis of axSpA. Further research integrating cytokine profiling with genetic and microbiome factors may improve early detection and individualized treatment strategies in axial spondyloarthritis.